2019
DOI: 10.31764/leltj.v12i2.749
|View full text |Cite
|
Sign up to set email alerts
|

The Speaking Difficulties Encountered by Non-English Students in Language Classroom

Abstract: This research, entitled “The Difficulties Encountered by Non-English Department Students in Speaking English,” was a study at the Faculty of Teacher Training and Education Muhammadiyah University of Mataram. It was conducted to investigate difficulties encountered by Non-English Department students in speaking. The participants were 15 students from the second semester of Indonesian Department Muhammadiyah University of Mataram. It also aims to investigate the factors which are face by Non-English department s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Some participants said: The findings were similar to some studies about problems in speaking class generally. Rahmaniah, Asbah, & Nurmasitah (2018) said that students faced several aspects of problems in speaking English. There were vocabulary, grammar, pronunciation, fluency, and comprehension aspects.…”
Section: Problems In Speaking Skillsmentioning
confidence: 99%
“…Some participants said: The findings were similar to some studies about problems in speaking class generally. Rahmaniah, Asbah, & Nurmasitah (2018) said that students faced several aspects of problems in speaking English. There were vocabulary, grammar, pronunciation, fluency, and comprehension aspects.…”
Section: Problems In Speaking Skillsmentioning
confidence: 99%
“…Pronunciation problem, the pronunciation problem is the greatest problem in learning English for student since among the students interviewed we found two students have adequate English Vocabulary, they could understand English written form and they also understand spoken language but they could not pronounce the words well. Rahmaniah et al (2018) reported that in English speaking classes, the majority of non-native English learners have a heavy accent and poor pronunciation, this make them difficult to understand.…”
Section: Difficulty Faced By Studentsmentioning
confidence: 99%
“…This is because English language is a complex subject for Indonesian students for it has four main skills to acquire. These skills can be grouped into two categories, namely the receptive and productive aspects (Rahmaniah & Asbah, 2019). The receptive aspect is acceptance or absorption, as seen in listening and reading activities.…”
Section: Introductionmentioning
confidence: 99%